Reflections about a Single Checksum - (:unkn) unknown (SPRINGER-VERLAG BERLIN, 2010)
A single checksum for codes consisting of n integer components is investigated. In coding theory this is mostly used for single error correction in unconventional error models. If the errors are such that a single component c(i) is distorted to c(i)+/-e(i), the analysis leads to equivalent group factorizations. We shall present several code constructions for this model, give a short survey on the coding theoretical and mathematical background, and also emphasize applications in cryptography and computer science.
Keywords: single - error correction; perfect codes; group factorization; steganography; distributed computing; PERFECT CODES; 3 CYCLES; PACKING; PRODUCTS